(In reply to
Problem Solution : Method II by K Sengupta)
Rewriting the equation as:
AM - MA = A, we obtain:
9(A-M) = A.....(*)
Clearly, A and M cannot be equal as these must denote separate digits.
If A- M >=2, the rhs in (*) contain more than one digit. Contradiction.
If A- M <= -1, then rhs of (*) is negative, which is a contradiction.
Since A-M cannort be 0, it follows that: A-M =1, giving A =9, so that M =8
Consequently, M and A respectively represent the digits 8 and 9 and the completed cryptarithm is: 89+9=98
Edited on January 21, 2023, 6:59 am